Applied Technology Integration in Governmental Organizations
DOI: 10.4018/978-1-60960-162-1.ch018
|View full text |Cite
|
Sign up to set email alerts
|

Leaders as Mediators of Global Megatrends

Abstract: The idea of eGovernment is moving rapidly within supra-national and national and local institutions. At every level leaders are interpreting the idea, attempting to grasp either the next step or indeed the very essence of the idea itself. This chapter outlines a diagnostic framework, resting on three different dimensions; translation, interpretative frames and sensemaking, to create knowledge about the translation processes and by doing so, emphasize enactment rather than vision. The diagnostic framework is th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…As research has already shown that many of the problems associated with the implementation of IT have to do with the frames of reference held by the members of the organisation and that their commitment to the implementation of IT is crucial for putting transformation into practice (Weick, 2001; Ebbers and van Dijk, 2007; Contini and Lanzara, 2009; Giritli‐Nygren and Lindblad‐Gidlund, 2009; Giritli‐Nygren, 2010), our framework provides an interesting source of an explanation regarding the difficulties and unforeseen outcomes associated with IT innovation and transformational government.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As research has already shown that many of the problems associated with the implementation of IT have to do with the frames of reference held by the members of the organisation and that their commitment to the implementation of IT is crucial for putting transformation into practice (Weick, 2001; Ebbers and van Dijk, 2007; Contini and Lanzara, 2009; Giritli‐Nygren and Lindblad‐Gidlund, 2009; Giritli‐Nygren, 2010), our framework provides an interesting source of an explanation regarding the difficulties and unforeseen outcomes associated with IT innovation and transformational government.…”
Section: Discussionmentioning
confidence: 99%
“…The background to the survey is that, when we approached the municipality (from a Swedish perspective a medium‐sized one with 95,000 inhabitants) several IT‐supported development projects had been implemented, or were about to be implemented and several actions were taken to initiate and distribute the idea of the desired transformation: various policy documents regarding eGovernment development were formulated and leaflets were produced explaining the ideas of eGovernment transformation (in which) they used the concept of 24‐hour government) to describe what was expected to be incorporated in different forms throughout the organisation. The study reported on here is, though, a part of a larger study also covering how the overarching idea of transforming government is translated on a management level, showing the importance of the idea being demythologised in order to be realised (Giritli‐Nygren and Lindblad‐Gidlund, 2009). As such, this study is a follow‐up concentrating on the mode of action in realisation terms, how those expected to perform the asked‐for transformation interpret their possibilities of acting and contributing (action space).…”
Section: Research Methods and Analytical Strategymentioning
confidence: 99%
See 1 more Smart Citation
“…The potential offered by electronic government is great [7]. What is talked about is that every promised benefit can be realized.…”
Section: The Role Of Stories In Policy Makingmentioning
confidence: 97%
“…We can have both increased efficiency and improved quality, simultaneously. Hence, there is no talk of contradictions between different goals [7]. Thus, to be able to move forward we need more nuanced stories.…”
Section: The Role Of Stories In Policy Makingmentioning
confidence: 98%